Effects of equivalent ratio and initial temperature on the explosion characteristics of ethanol, acetone, and ethyl acetate - Zhang, Kai; Chen, Sining; Li, Yanchao; Duo, Yingquan; Wei, Lijun (Frontiers in Energy Research, 2024)
In this paper, the effects of equivalence ratio (0.8-2.0) and temperature (30-120 °C) on ethanol, acetone, and, ethyl acetate vapors explosion characteristics through experimental and numerical studies were investigated. The explosion overpressure and flame propagation velocity were recorded through the pressure transducer and high-speed camera. The results showed that the flame propagation velocity, peak explosion overpressure, and peak growth rate of explosion overpressure increased first and then decreased with the increase of equivalence ratio. The cracks on the flame surface enhanced with the increase of the equivalence ratio. As the initial temperature increased, peak explosion overpressure, the flame propagation velocity, and peak growth rate of explosion overpressure gradually increased. The sensitivity analysis of laminar burning velocity indicated that with the change of equivalence ratio and initial temperature, the shared elementary reactions that increased the reactivity were H + O2 <=> O + OH, HCO + M <=> H + CO + M, and CO + OH <=> CO2 + H, and the shared elementary reaction that reduced the reactivity was H + OH + M <=> H2O + M. The main factor affecting laminar burning velocity was the mole fraction of H and OH radicals.